Temperature-driven nonclassical light - Pennini, Flavia Catalina (2013)
With reference to two well known scenarios, we discuss, for nonclassical light, the competition between quantum and thermal effects. It is seen that for nonclassical light to be produced some amount of temperatureinduced disorder is needed plus quantum fluctuations of order h squared.